Community Empowerment for Landslide Disaster Mitigation in Ngrancah Hamlet, Pendoworejo Village, Kulon- Progo District, Yogyakarta Special Region, Indonesia - Wilopo, Wahyu (Center for Water Cycle, Marine Environment and Disaster Management (CWMD) Kumamoto University, 2019)
Community empowerment in vulnerable areas of landslide in Ngrancah Hamlet, Pendoworejo Village, Girimulyo Subdistrict, Kulon Progo Regency, was motivated by the occurrence of landslide in early March 2018 that damaged residents' houses and road infrastructure. The objectives of the research are to know the geological condition, to understand the mechanism of landslide, and to recommend the mitigation action of landslide disaster. The method used is field survey that includes aerial observation, observation of soil and rocks and observation of signs of landslide and the delivery of research results to the community through socialization activities. The results show that the mechanism of landslide in Ngrancah Hamlet is influenced by geological conditions such as morphology, lithology and triggered by high rainfall. The landslide can be divided into two systems, the rotational sliding in the hills and creeping in the residential area. Community empowerment in the area is done by disseminating the result of study either directly or poster to increase knowledge and understanding of landslide to the society. So that communities and related agencies can perform mitigation actions such as filling the cracks with waterproof material, coating the existing pond with waterproof layers, developing drainage systems in hilly areas and residential areas, and cleaning up unstable material in the hills. In addition, installing a simple gauge from roll meter can be used to monitor of land movement. Finally, the community also has the ability to conduct an independent evacuation to face landslide disaster.